2021
DOI: 10.1177/08861099211055519
|View full text |Cite
|
Sign up to set email alerts
|

Practice in a Time of Uncertainty: Practitioner Reflections on Working With Families Experiencing Intimate Partner Violence During the COVID-19 Global Pandemic

Abstract: This paper reports findings of a qualitative study examining the perceptions of 21 Australian women professionals who conduct home visiting with families experiencing intimate partner violence. There is scant evidence documenting how home visiting professionals adapted practice to address the safety concerns of women and their children within the context of the pandemic. Practitioners noted an increase in the risk level and complexity of intimate partner violence (IPV), including the ways that perpetrators wea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 28 publications
0
16
0
Order By: Relevance
“…Our findings help unveil the ways we may think about drastically addressing the workplace stressors and “fragile systems” (Heward-Belle et al, 2021, p. 10) associated with gendered, high-stress workplaces—and remind us not to remain complacent with a return to pre-pandemic resources. If the coping strategies in a frontline worker's toolkit become imbued with a new layer of stress and strain, they may fail to adequately protect against burnout, especially in social welfare sectors like anti-violence service provision, where exhaustion and re-traumatization are often looming (Baird & Jenkins, 2003).…”
mentioning
confidence: 80%
See 3 more Smart Citations
“…Our findings help unveil the ways we may think about drastically addressing the workplace stressors and “fragile systems” (Heward-Belle et al, 2021, p. 10) associated with gendered, high-stress workplaces—and remind us not to remain complacent with a return to pre-pandemic resources. If the coping strategies in a frontline worker's toolkit become imbued with a new layer of stress and strain, they may fail to adequately protect against burnout, especially in social welfare sectors like anti-violence service provision, where exhaustion and re-traumatization are often looming (Baird & Jenkins, 2003).…”
mentioning
confidence: 80%
“…This article reflects research conducted in service of understanding the nuances of anti-violence service provision during COVID-19. We situate this project alongside Quinlan and Singh's (2020) exploration of Canadian domestic violence service provision and Heward-Belle et al's (2021) interviews with anti-violence health professionals in Australia. Author 1 and Author 2 joined to explore how the dual impacts of COVID-19 spread and mitigation strategies affected service providers in the anti-violence 3 sector.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Heightened vulnerabilities and an eroding capacity to withstand unrelenting changes and acceleration have occupied many pages of journals, including ours (Kim et al, 2021). Critical feminist research showed us how the pandemic disproportionately threatened the lives and well-being of Latinx immigrants (Cross & Gonzalez Benson, 2021), Latina immigrants (Cleaveland & Waslin, 2021), sex workers (Bromfield et al, 2021), intimate partner violence survivors (Heward-Belle et al, 2022), student mothers (LaBrenz et al, 2023), trafficking survivors (Namy et al, 2023), and anti-violence workers (Welch & Schwarz, 2023). Social work scholars like Stephanie Lechuga-Peña (2022) showed us how pandemic conditions disproportionately impacted the “productivity” of pre-tenure BIPOC junior women faculty.…”
mentioning
confidence: 99%